Comparing corn silage with beet pulp silage fed separate or mixed with concentrate in buffalo calves - Abdur Rahman; Ali R. Khan; Muhammad I. Anjum; Zafar Hayat; Muhammad Arshad (Revista Científica)
Twelve male calves of Nili-Ravi buffalo (aged 14 ± 2 months and weighing 133 ± 5 kg) were randomly assigned one of four experimental diets. Group A was fed only concentrate in the morning and corn silage in the afternoon. Group B was offered a total mixed ratio (TMR) of corn silage. Group C was fed only concentrate in the morning and then beet pulp silage in the afternoon. Group D was given TMR of beet pulp silage. A 2X2 factorial design was applied in this study. Concentrate was formulated with 17% CP and used in a ratio of 50:50  concentrate and silage, respectively. All diets were iso-nitrogenous and iso-caloric. Data was presented as  means and SE. The data was statistically evaluated by Minitab 15 software using analysis of variance in a completely randomized design. The p-value used to compare the significance was set at ≤0.05. Results showed that Group D, fed TMR of sugar beet pulp silage with concentrate, gained significantly more daily weight than other groups. The highest daily weight gain in grams was observed in Group D (852±0.03), followed by Group C (755±0.03), Group B (741±0.03) and Group A (758±0.03). There were no significant differences in feed intake. However, the feed conversion ratio revealed significant improvement in Group D (5.913±0.81) followed by Group C (6.391±0.81), Group B (6.467±0.81) and Group A (6.535±0.81). The digestibility values of dry matter (DM), crude fiber (CF), and crude protein (CP) were significantly better in groups B and D. The digestibility values of DM, CP, and CF were 66.37±2.01, 69.55±1.25, 63.15±1.12 in Group B and 65.90±2.01, 68.55±1.25, 62.33±1.12 in Group D respectively. The significantly highest value of nutrient digestibility of neutral detergent fiber (66.12±1.67) and acid detergent fiber (60.15±1.78) was observed in Group D. The nitrogen intake and retention by all the treatment groups showed non-significant differences. Regarding serological examination, cholesterol levels showed significantly lower values in Group D, while blood glucose and urea nitrogen exhibited no differences. In the economic analysis, the costs of the different groups were calculated, and it revealed that beet pulp silage and concentrate TMR were economically favorable for the fattening of calves in terms of input-to-output ratio. The better results in group D might be due to the synergic effect of sugar beet pulp silage and concentrate by improving the digestibility of nutrients and their effective utilization. In conclusion, sugar beet ensiled with ground corn cobs is a simple and viable strategy for effective silage making. However, sugar beet pulp silage with concentrate TMR had a pronounced economic impact on the fattening of buffalo calves in terms of cost-to- gain ratio.